2021
DOI: 10.4103/jfmpc.jfmpc_666_21
|View full text |Cite
|
Sign up to set email alerts
|

APRI and FIB-4 performance to assess liver fibrosis against predefined Fibroscan values in chronic hepatitis C virus infection

Abstract: Backgrounds and Aims: Chronic hepatitis C (CHC) infection can leads to chronic liver disease, fibrosis, then cirrhosis, and, finally, hepatocellular carcinoma (HCC); moreover, it is the most common indication for liver transplantation. Liver biopsy is still the gold standard method for the staging of liver fibrosis as it is an invasive procedure with complications. There are some noninvasive methods such as fibroscan that are now the investigation of choice; FIB-4 and aminotransferase to platelet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…It also works to detect smaller changes as the disease progresses and the liver deteriorates [48]. Closely associated with this index are typical fibrosis scores, such as FIB-4 (formula: age [years] * AST [IU/L]/platelet count [10 9 /L] * ALT [IU/L] 1/2 ) as well as the AST to platelet ratio index {APRI; formula: [AST (IU/L)/upper normal limit of AST (IU/L)]/platelet count [10 9 /L]} [49].…”
Section: Surgical Managementmentioning
confidence: 99%
“…It also works to detect smaller changes as the disease progresses and the liver deteriorates [48]. Closely associated with this index are typical fibrosis scores, such as FIB-4 (formula: age [years] * AST [IU/L]/platelet count [10 9 /L] * ALT [IU/L] 1/2 ) as well as the AST to platelet ratio index {APRI; formula: [AST (IU/L)/upper normal limit of AST (IU/L)]/platelet count [10 9 /L]} [49].…”
Section: Surgical Managementmentioning
confidence: 99%
“…Additionally Rungta et al's (2021) research explored the efficacy of the Aspartate Aminotransferase to Platelet Ratio Index, also known as APRI and the Fibrosis-4 or FIB-4 indices in evaluating liver fibrosis. Findings shed light on non-invasive methods for assessing liver health, particularly in cases of chronic hepatitis C virus infection [22] and in a separate study, Fan et al (2018) conducted a comprehensive dose-response analysis with the aim of elucidating the correlation between BMI and the likelihood of developing fatty liver. Their research provides nuanced perspectives on the complex interplay between obesity and liver well being [23] .…”
Section: Introductionmentioning
confidence: 99%
“…5 Recent studies have found that compared with TE, the aminotransferase-platelet ratio index (APRI) and fibrosis score 4 (FIB-4) showed satisfactory performance in detecting significant fibrosis in LT recipients and chronic hepatitis C (CHC) virus infection, and could be used as an estimate of significant fibrosis at centers where TE was not available. 6,7 However, few clinical studies are available on the evaluation and diagnosis of post-LT hepatic fibrosis using APRI and FIB-4, compared with TE. This study aimed to evaluate the effectiveness of APRI and FIB-4 in assessing liver fibrosis after LT, compared with TE.…”
mentioning
confidence: 99%
“…Several studies have found that novel noninvasive diagnostic techniques, such as TE and acoustic radiation force impulse (ARFI), could accurately detect hepatic steatosis and fibrosis in LT recipients and patients with chronic liver disease. 8-10 Rungta et al 6 found that APRI and FIB-4 showed satisfactory performance in detecting significant fibrosis in patients with CHC infection, compared with TE. 6 According to Nishimura et al, 11 the diagnostic performance of APRI and FIB-4 was inferior to that of ARFI, in the chronic hepatitis B (CHB) and CHC cohorts.…”
mentioning
confidence: 99%
See 1 more Smart Citation